Biodiesel from Wastelands: Economics of Jatropha curcas and Pongamia pinnata Cultivation in India - Karmakar, K.G.; Haque, M.S.; Kannapiran, S. (Indian Journal of Agroforestry, 2020)
The Planning Commission has identified Jatropha curcus and Pongamia pinnata as the most suitable and promising species for biodiesel production. Realizing the potential of both these trees in meeting national objectives of wasteland development, substituting costly liquid fuel and rural employment generation, National Bank for Agriculture and Rural Development (NABARD) has formulated model bankable schemes after visiting old existing plantations in various research organisations and also collected data from different regional offices of NABARD. For J. curcus, it recommends spacing of 2 m x 2 m accommodating 2500 trees per ha. The unit cost of cultivation is Rs. 30,000 per ha over a period of 3 years. The plantation will be raised through seeds and commercial yield will start from 3rd year with production of 0.5 kg seed per tree, increasing to 2.0 kg by 7th year, which will continue to produce at least for 30 years. Application of fertilizers weeding, soil working and pruning have been recommended in the scheme. The model scheme has been found to be both technically feasible and financially viable. The IRR (internal rate of return) of the scheme is 30% thus making it bankable: The sale price of seeds is assumed to be Rs. 5 per kg. With sensitivity analysis of 5% cost increase and decrease in income, the IRR is 27 %, the same with 10% increase in cost and decrease in income is 25 %. Intercropping is also suggested, however while calculating economics, income from intercropping has not been considered. One haÂ Jatropha plantation will create employment of 138 in first year, 65 in second year and 34 in third year. Pongamia pinnata is a big tree with long life, hence the spacing recommended for raising commercial plantations is 5 m x 4 m accommodating 500 trees per ha. Because of wide spacing, the farmers can practise intercropping for many years. Besides, the tree is a leguminous and fixes atmospheric nitrogen, which improves soil fertility. The estimated unit cost for cultivation is Rs. 19,000 per ha over a period of 5 years. The plantation will start commercial yield in 6’h year when 6 kg seeds will be available per tree and which will stabilize at 20 kg per tree by 11Ih year. Considering the sale price of fruits at Rs. 5 per kg and based on the estimated unit cost of cultivation and projected yield, the IRR of the scheme is 35.06%. The sensitivity analysis with 5 % increase in cost and decrease in income gives an IRRof33%. The same with 10% increase in cost and decrease in income gives an IRR of 27%. Our estimates on cost of cultivation, sale price of produce and income are not only realistic but also conservative. The scheme is both technically feasible and financially viable. One ha Pongamia plantation will create employment at the rate of 105,51 and 51 mandays in first, second and third years. Based on these models NABARD is making vigorous efforts to promote bankable bio-diesel projects in the potential states of Andhra Pradesh, Tamil Nadu, Chattisgarh, Uttaranchal, Madhya Pradesh, Uttar Pradesh and North-Eastern states. NABARD has already sanctioned a big biofuel project under RIDF (Rurallnfrastructural Development Fund) with loan of Rs. 30.52 crores to Andhra Pradesh state Govt. for raising Pongamia plantation in 15,000 ha of degraded lands covering 15 Districts.